Nitrogen and dry matter production of "common" annual ryegrass - Gonçalves, José Otávio Neto (Pesquisa Agropecuaria Brasileira, 2014)
The effect of five levels of nitrogen (0, 50, 100, 150 e 200 kg N/ha) on the dry matter production of "common" annual ryegrass (Lolium multiflorum Lam.) was studied during a two-year period. The experiment was carried out at field conditions in the UEPAE - Cinco Cruzes - EMBRAPA, Bage, Southwest of Rio Grande do Sul – Brazil. The soil under the experiment is mapped as a Planosolo Vértico. Urea was used as the nitrogen source. The treatments were arranged in randomized blocks design with four replications. Results showed that "common" annual ryegrass dry matter yields - increased with nitrogen application. However, dry matter yields were not proportionally increased when higher levels of nitrogen were applied. For the experimental conditions here defined, the level of 50 kg N/ha was the most efficient.